2019
DOI: 10.1186/s12903-019-0981-4
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prophylaxis prescribing habits in oral implant surgery in the Netherlands: a cross-sectional survey

Abstract: BackgroundThere seems to be no consensus on the prescription of prophylactic antibiotics in oral implant surgery. The Dutch Association of Oral Implantology (NVOI) guidelines do not include a clear policy on prophylactic antibiotic prescriptions for oral implant surgery among healthy patients. The purpose of the study was to determine whether antibiotic prophylaxis is commonly prescribed in the Netherlands by general dentists, maxillofacial surgeons and oral implantologists in conjunction with oral implant sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 18 publications
3
36
2
1
Order By: Relevance
“…There are also similar studies from different countries in the literature. Sanchez et al conducted a cross-sectional questionnaire among dentists and specialists in Netherland and like in this study, they concluded that there was no consensus regarding prescribing antibiotics related to implant surgery and the clinicians were preferring to prescribe antibiotics even if it is not recommended in the guidelines [26].…”
Section: Discussionmentioning
confidence: 63%
“…There are also similar studies from different countries in the literature. Sanchez et al conducted a cross-sectional questionnaire among dentists and specialists in Netherland and like in this study, they concluded that there was no consensus regarding prescribing antibiotics related to implant surgery and the clinicians were preferring to prescribe antibiotics even if it is not recommended in the guidelines [26].…”
Section: Discussionmentioning
confidence: 63%
“…Five cross-sectional surveys were finally included in this meta-analysis [21][22][23][24][25]. Table 1 shows the descriptive information for of each study included in the quantitative analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies were judged as being of moderate quality [21][22][23][24][25] and one of low quality [22]. The percentage of affirmative answers to the National Health Index checklist was 75% for the study performed in Sweden, 54.5% for the other 3 studies (Spain, the Netherlands and Italy) and 45.5% for the study performed in the United Kingdom.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations